Online e-Book maker - Ang, Wei Di (2024)

(untitled)
The title of this project is called “Online e-Book Maker”. This project is conducted because of the bright future of the eBook industry. According to the expert analysis, the eBook market size is expected to increase which means growth in eBook demand. However, the existing systems unprepared for the forecasting since there are crucial problems discovered in existing system. The main objective is to solve the problem, enhance the system and ultimately provide better user experience. This project adopts phased development under Rapid Application Development to manage the lifecycle of development process to shorten development time and establish quality product within the planned timeline. The development was carried out using software such as Visual Studio 2022 which use ASP.NET(VB.NET/C#), HTML and JavaScript for coding the final product. Additionally, technologies like Microsoft Azure were utilized for deployment, GitHub for version management and various online libraries for functionalities development. The final developed system integrates document analysis and questionnaires as the primary techniques for gathering information to understand market benchmarks, user requirements, and satisfaction levels. This approach enables the system to integrate the advantages of the existing system while solving those weaknesses to better serve the target audiences like senior citizens and novice users. It comprises four main modules covering the core aspects which are builder module, tools module, interface module and security module. These modules are depicted through diagrams like architecture, entity relationship, use-case, activity, and wireframe diagram to understand the interconnection of the systems’ components, data storage, functionalities, process, and user interface. Subsequently, the system flow is demonstrated to show the project functionalities. while remarking the implementation issues and challenges After conducting black box testing and user testing, the system is evaluated and found to achieve a satisfactory result with a perfect achievement rate for the objective assessment Finally, the project development is concluded through reviewing the whole project and highlighting both its limitations and potential future enhancements.